Hydrocarbon Tax and Profitability of Listed Oil and Gas Firms in Nigeria - Timothy Aondona Aondover (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
For more than five decades, Nigeria’s fiscal framework and macroeconomic stability have been shaped by the oil and gas industry, with petroleum revenues providing nearly 80% of government income and 90% of foreign exchange earnings. Central to this fiscal system is taxation, particularly the Petroleum Profits Tax (PPT), which has historically imposed one of the highest corporate tax burdens globally, reaching up to 85% of chargeable profits. While such taxes are indispensable for public revenue mobilization, they also raise concerns about profitability, investment incentives, and long-term sustainability of oil and gas firms. This study investigates the relationship between petroleum taxation and the profitability of Nigerian listed oil and gas companies, with a focus on the transition from the long-standing PPT regime to the dual Companies Income Tax (CIT) and Hydrocarbon Tax (HT) introduced by the Petroleum Industry Act (PIA) of 2021. Using secondary data and descriptive analysis, the study evaluates how tax policy, compliance requirements, and fiscal reforms influence firm-level financial performance. The findings highlight the dual role of taxation as both a revenue driver for government and a profitability constraint for firms, showing that high effective tax rates may discourage investment, compress margins, and intensify compliance costs. However, the restructured tax system under the PIA has potential to foster a more transparent and investor-friendly fiscal environment. By bridging the gap between fiscal policy and firm performance, this research contributes to ongoing debates on balancing government revenue needs with corporate sustainability in Nigeria’s oil and gas sector.